Does Short-Time Work Save Jobs? A Business Cycle Analysis - Christian Merkl; Almut Balleer; Britta Gehrke; Wolfgang Lechthaler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper analyzes the effects of short-time work (i.e., government subsidized working time reductions) on unemployment and output fluctuations. The central question is whether short-time work saves jobs in recessions. In our baseline scenario the rule based component of short-time work (i.e., due to the existence of the institution) stabilizes unemployment fluctuations by 15% and output fluctuations by 7%. Given the small share of short-time work expenses in terms of GDP, the stabilization effects are large compared to other instruments such as the income tax system. By contrast, discretionary short-time work interventions (i.e., rule changes) do not have any statistically significant effect on unemployment. These effects are based on a SVAR estimation,which uses an elasticity of the German establishment panel for identification purposes. The model shows that non-effects of discretionary interventions (i.e., 100% deadweight) may be due to their low persistence.
Keywords: E32; E02; E24; 330